Peran Psychological Stress sebagai Mediator pada Pengaruh Leader-Member Exchange dan Perceived Organizational Support terhadap Job Performance Dosen PTS di DKI Jakarta - Dewi Trirahayu; Ade Wahyudi; Indra Ade Irawan; Maharani Ardi Putri; Adytama Nurrohmat A.S (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the role of Psychological Stress as a mediator in the effects of Leader-Member Exchange and Perceived Organizational Support on lecturers' Job Performance at private higher education institutions in DKI Jakarta. The research was motivated by the increasing complexity of lecturers' work, including teaching, publication, community service, accreditation, academic administration, and digital system adaptation. This study used an explanatory quantitative approach with a survey design. Data were collected from 200 active private university lecturers selected using convenience sampling with screening criteria. The instrument used a five-point Likert scale and was analyzed using Partial Least Squares Structural Equation Modeling. The measurement model met convergent validity, discriminant validity, and reliability criteria. The R-square value was 0.497 for Psychological Stress and 0.601 for Job Performance. Hypothesis testing showed that Psychological Stress positively affected Job Performance. Leader-Member Exchange and Perceived Organizational Support also positively affected Job Performance. Psychological Stress significantly mediated the effects of Leader-Member Exchange and Perceived Organizational Support on Job Performance. These findings indicate that high-quality leader-lecturer relationships and institutional support improve lecturer performance directly and through work pressure perceived as a manageable challenge. The study contributes to human resource management in higher education by showing that productive work pressure requires leadership support, organizational support, and workload governance.